The Role of Human Resource Management Practices on Promoting Organizational Citizenship Behavior from an Islamic Perspective - Mohsen Akbari; Masoomeh Ghasemi Shams; Hani Nikookar (مطالعات منابع انسانی, 2019)
Organizations today need employees who behave beyond the roles described in the organizational job description in order to improve their effectiveness and efficiency and the realization of their own vision and mission statement, something that is now called OCB. Of course, the importance of this in service organizations such as the police is twofold. On the other hand, the original religion of Islam is the highest and best Life and Action Plan and has unique potentials that human resource management can do more effectively with its implementation and improve post-role behaviors in employees. The purpose of this paper is to study the role of human resource management practices in the light of Islamic teachings to improve organizational citizenship behavior. In this paper, firstly, organizational citizenship behavior and human resource management from the point of view of Islam and then the role of Islamic human resources management in strengthening organizational citizenship behavior were discussed. The results showed that Islam is full of teachings that have a tremendous capacity to enhance and improve the desirable behaviors of employees and if each of the human resources management sub-systems, namely, recruitment and selection, training and development, compensation, rewards and performance appraisal implemented taking into account the teachings of the school of Islam, the Quran and the Ahlul-Bayt, will further enhance and improve organizational citizenship behavior and ultimately lead to organizational effectiveness.